Serum Zinc status in patients with haemoglobin-E ? thalassemia - Morshed, AKM Amirul; Islam, Shahnoor; Chowdhury, Tasrina Rabeya; Islam, Afiqul; Islam, Ariful; Begum, Helena; Haq, Sheikh Azimul; Dey, Pritam (Journal of Dhaka Medical College, 2015)
Background: Hb-E â thalassemia is a major congenital hematological disease of Bangladesh. The patients have poor growth and delayed maturation mainly due to iron overload but zinc deficiency also has been suggested as a contributing factor. The aim of this study was to investigate and compare the serum zinc of HbE-â thalassemia patients and normal children. Methods: This cross sectional study was done in the Department of Paediatric Haematology and Oncology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from July 2009 to May 2010. A total of 31children with Hb-E â thalassemia were enrolled for this study and besides, matched 30 healthy children were taken as control. After initial assessment the cases were thoroughly examined by the investigators and history of transfusion, transfusion interval were recorded. Venous blood samples (3mL) were drawn from patients and normal control children then centrifuged and stored at -20°C until analyzed. Serum level of zinc was measured by using Flame Atomic Absorption Spectrophotometry. Results: Mean serum zinc level in thalassemic group and control group were 97.4?g/dl (SD- 18.4) and 99.6?g/dl (SD-18.7) respectively. There is no significant difference between two groups (p=0.47). Conclusion: It may be concluded from this study that serum zinc level did not significantly change in children with Hb-E â thalassemia DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21518 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 115-119